Behavioral Factors Affecting the Home Bias Phenomenon: Experimental Tests. Issue 3 (2nd July 2016) - Riff, Sivan; Yagil, Yossi
ABSTRACT: Although international portfolio theory states that an optimal portfolio should be well diversified, in practice, investors tend to invest excessively in domestic assets. This tendency, which is commonly referred to in the finance literature as "home bias" (HB), has puzzled economists for many decades. This research develops and presents experiments designed to test the behavioral factors related to HB discussed in the literature. In particular, these experiments test whether the factors of "familiarity" and "fluency" (ease of pronunciation) affect HB. In addition, using a method of controlled experiments, we examine the willingness to take risk as a basic source of HB. We also examine HB under three different market conditions (normal, bear and bull markets). Results indicate that subjects tended to take less risk with foreign, unfamiliar and nonfluent (difficult to pronounce) assets compared with local, familiar and fluent assets. This tendency increased significantly when the three factors were present together (foreign, unfamiliar and nonfluent assets) compared with when only one of the three factors was present. The results also revealed that HB increased during bear market periods.